Pippi Longstocking - Lindgren, Astrid, 1907-2002.; Glanzman, Louis S., 1922- (New York, Viking Press, 1950)
Escapades of a lucky little girl who lives with a horse and a monkey--but without any parents--at the edge of a Swedish village.
Translation of: Pippi Långstrump.
G6
Keywords: Humorous stories